Evaluation of Olive Pruning Effect on the Performance of the Row-Side Continuous Canopy Shaking Harvester in a High Density Olive Orchard - Dias, António Bento; Falcão, José M.; Pinheiro, Anacleto; Peça, José O. (Frontiers in Plant Science, 2020)
In 2009, the Side-Row Continuous Canopy Shaking Harvester project was set to develop such technology. The prototype comprises two symmetrical harvesters trailed by a farm tractor. Each harvester has a vibratory rotor with flexible rods, a catching platform with conveyors belts delivering fruits to a temporary storage bag. The removal efficiency of canopy shakers are influenced by factors like shaking frequency, ground speed as well as the dimension and shape of olive canopy. In 2014 authors started a trial to evaluate the influence of pruning in olive yield and in the performance of the Side-Row Continuous Canopy Shaking Harvester. The trial was established in an irrigated olive orchard of Picual cultivar planted in 1996 with the array 7 m x 3.5 m. In a randomised complete block design with three replications, four treatments are being compared leading to 12 plots with 30 trees/plot. The treatments under study are: T1—manual pruning using chain saws, in 2014 and 2017; T2—mechanical pruning: topping and hedging the two sides of the canopy, followed by manual pruning complement to remove wood suckers inside the canopy, in 2014 and 2017; T3—mechanical pruning: topping the canopy parallel to the ground and hedging southeast side of the canopy in 2014 and 2017; topping the canopy in July 2015 (summer pruning); hedging northwest side in winter 2016; T4—mechanical pruning: topping and hedging the two sides of the canopy in 2014 and 2017; topping the canopy in July 2015 (summer pruning). Regarding to olive yield per tree, significant differences were found among treatments on different years. However, no significant differences were found regarding the average olive yield per tree, over the period of 2014–2017. Regarding to the olive removal efficiency, only in 2016, significant differences were found among treatments on different years. No significant differences were found regarding the average of the olive removal efficiency, over the period of 2014–2017.